A study of the impact of ergonomically designed workplaces on employee productivity - Leber, Marjan (Advances in production engineering and management, 2018)
Ergonomics principles help designing the workplace in a way that makes work more efficient and safer. Employee satisfaction increasingly affects the productivity of a process, which also includes disabled people and represents an important source of human resources. In the framework of the EU-project ERGO WORK a survey-based research was conducted to measure the satisfaction of people with disabilities (PWD) in their workplace and asses how their satisfaction was perceived by employers in UK, Poland and Slovenia. Three hundred and three respondents were involved in the survey. Results show that PWD place a great emphasis on the satisfaction in the workplace. PWD in Slovenia are more satisfied than PWD in Poland, whereas the employers' perception of the satisfaction of PWD and other employees in Poland, Slovenia and UK does not vary. A general adaptation of the workplace significantly and positively influences the satisfaction of persons with disability and that the adaptation of the workplace to the needs of PWD is better if employers have access to knowledge, special equipment and financial resources.
Keywords: delovno okolje; ergonomija; osebe s posebnimi potrebami; produktivnost; zadovoljstvo